The effect of vaccination beliefs regarding vaccination benefits and COVID-19 fear on the number of vaccination injections - Hoang, Hai The; Nguyen, Xuan Thanh Kieu; Huynh, Son Van; Hua, Thuy Doan; Tran, Hien Thi Thuy; Tran-Chi, Vinh-Long (Frontiers in Psychology, 2022)
The Coronavirus disease pandemic of 2019 is a vast worldwide public health hazard, impacting people of all ages and socioeconomic statuses. Vaccination is one of the most effective methods of controlling a pandemic like COVID-19. This study aims to investigate the relationship between the number of vaccination injections and fear of COVID-19 and test whether beliefs benefit from vaccination COVID-19 mediate the effect of fear of COVID-19 on the number of vaccination injections. A total of 649 Vietnamese adults were enrolled online to finish answering, including scales The Health Belief Model (HBM) and The Fear of COVID-19 (FCV-19S), consisting of 340 (52.4%) males and 309 (47.6%) females. The data were analyzed using variance, regression, and a simple mediation model. The total score of COVID-19 fear was (M= 22.26, SD= 5.49). Vietnamese fear of COVID-19 was at a medium level. Our results suggest that 18 to 20-year-olds are more fearful of COVID-19 than others. People who received the first dosage exhibited a greater fear of COVID-19 than those who received the second dose and were not inoculated. Additionally, the Beliefs benefit of vaccination COVID-19 has a role in the relationship between the number of vaccination injections and fear of COVID-19. During the pandemic, adults in Vietnam are more afraid of COVID-19 than during prior outbreaks. Besides, the Vietnamese populace demonstrated a considerable demand for and high acceptability of the COVID-19 vaccine. The current study indicates that psychological counselors and therapists should counsel clients on the value of vaccination and address the fear of COVID-19 as public understanding of the benefits of vaccines increases. To further clarify the effect of this issue on the correlation between fear of COVID-19 and the number of vaccinations, the results of this study indicate that the existing vaccine communication factor for COVID-19 vaccination should be modified to increase confidence in the benefits of immunization.